Clima organizacional y su relación con el desempeño laboral de los colaboradores en la comercializadora La Parada, distrito de Iquitos 2022 - Garcia Piña, Mary Carol (2022)
The objective of this research is to determine the relationship between Organizational Climate and the Labor Performance of the collaborators in Comercializadora la Parada, district of Iquitos 2022, the type of Correlational research and cross section of quantitative approach was used, the population is made up of 20 collaborators of Comercializadora la Parada, district of Iquitos 2022, the survey was conducted to the 20 employees of the company, a Pearson correlation of the data collected with the survey equal to 0.841** was obtained; this indicates that variable 1 and variable 2 have a considerable positive correlation and according to the sigma value (bilateral) equal to 0.000, it was determined that this correlation is significant. The data on the dimensions of variable 1: Organizational climate allowed us to determine that 100% of workers consider that this variable has the category of good, the same situation corresponds to variable 2 work performance. The investigation concluded that according to the calculated Pearson correlation value of the data collected with the survey regarding the two variables, it is equal to 0.841; In addition, the value of bilateral sigma is equal to 0.000, being less than 0.05 by decision rule, we conclude that there is a significant relationship between Organizational Climate and the Labor Performance of the collaborators in Comercializadora la Parada, district of Iquitos 2022.